Pengaruh Wisata Desa Adat Osing Terhadap Peningkatan Pendapatan Keluarga Masyarakat Kemiren Banyuwangi - Estu Handayani; Tintin Harlina (STIE Mandala Jember, 2021)
The development of tourism in Banyuwangi has a very significant effect on improving the economy of the community, especially in the village of Kemiren. With the increasing number of tourist visits to the Osing traditional village, it will also affect the increase in the family income of the Kemiren village community. The economic influence due to tourism cannot always be enjoyed by all levels of society who live in the tourist area, sometimes there are components that do not enjoy it either individually or in groups. From this background an analysis was carried out on